2019
DOI: 10.2217/fon-2019-0421
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting the Randomized Controlled Trial with Real-World Data to Aid Clinical Decision Making in Metastatic Renal Cell Carcinoma: A Systematic Review and Meta-Analysis

Abstract: Aim: To evaluate how efficacy outcomes from real-world data (RWD) can support those from randomized controlled trials (RCTs), in the context of first-line tyrosine kinase inhibitor treatment of metastatic renal cell carcinoma. Patients & methods: PubMed, Ovid, MEDLINE and EMBASE were searched for RCTs and RWD studies with ≥50 adult patients per arm published in 2000–2017. Outcome measures were median progression-free survival, median overall survival and objective response rate. Results: A total of 13 RCTs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…The efficacy of the mRCC treatments in clinical trials appeared to be similar to the reported effectiveness in observational studies. This is consistent with other analyses, which suggest a role for real-world data as a complementary source of evidence to RCTs to aid clinical decision-making [24]. The exception may be the ORR for sunitinib reported by Di Giorgi et al [25], which appeared to be substantially higher than that reported in clinical trials.…”
Section: Discussionsupporting
confidence: 88%
“…The efficacy of the mRCC treatments in clinical trials appeared to be similar to the reported effectiveness in observational studies. This is consistent with other analyses, which suggest a role for real-world data as a complementary source of evidence to RCTs to aid clinical decision-making [24]. The exception may be the ORR for sunitinib reported by Di Giorgi et al [25], which appeared to be substantially higher than that reported in clinical trials.…”
Section: Discussionsupporting
confidence: 88%
“…In this respect, there may also be an increase in the number of real-world data analyses published. Available studies suggest that data from randomized controlled trials are generally consistent with those of real-world data, which may provide complimentary evidence to inform treatment selection [65][66][67][68].…”
Section: Expert Opinionmentioning
confidence: 86%
“…Patients with mRCC seen in everyday clinical practice are more likely to have poor-risk disease and impaired performance status compared with phase III trial participants; this may have an impact on the variation in post-trial reported survival outcomes [18]. Reassuringly, meta-analyses have shown that overall and progression-free survival with TKI therapy in real-world datasets and clinical trials are remarkably similar [22,23].…”
Section: Real-world Data In Mrccmentioning
confidence: 99%